Memory disambiguation hardware: a review - Castro, Fernando (2008)
One of the main challenges of modern processor designs is the implementation of scalable and efficient mechanisms to detect memory access order violations as a result of out-of-order execution. Conventional structures performing this task are complex, inefficient and power-hungry. This fact has generated a large body of work on optimizing address-based memory disambiguation logic, namely the load-store queue. In this paper we review the most significant proposals in this research field, focusing on our own contributions.